Copper-catalyzed regioselective 2-amination of o-haloanilides with aqueous ammonia. (13th April 2021) - Tang, Yan-Ling; Li, Mei-Ling; Gao, Jin-Chun; Sun, Yun; Qu, Lu; Huang, Feng; Mao, Ze-Wei
Graphical abstract: An efficient Cu(II)-vasicine catalytic system has been developed for intramolecular CN bond formation. In this way, regioselective 2-amination of o -haloanilides with aqueous ammonia in EtOH. This strategy provides several advantages, such as good regioselectivity, high yields and functional group tolerance. Highlights: Regioselective 2-amination of o -haloanilides. Preparation of 2-aminoanilides in high yields. Functional group tolerance and mild condition. Abstract: An efficient Cu(II)-vasicine catalytic system has been developed for intramolecular CN bond formation. In this way, regioselective 2-amination of o -haloanilides with aqueous ammonia in EtOH has been achieved. This strategy provides several advantages, such as good regioselectivity, high yields and functional group tolerance.